Implementasi Pembelajaran Pendidikan Jasmani Melalui Aktivitas Senam Irama dan Permainan di SD Swasta Muhammadiyah 11 Medan - Suyono; Mutia Ulfa; Aisah Anggriani Butar-Butar; Hafizotul Husna; Nur Adilah Nasution (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2026)
This study aims to describe the implementation of physical education learning through gymnastics and games at SD Swasta Muhammadiyah 11 Medan. A qualitative approach was employed using interviews and documentation as data collection techniques. The findings indicate that physical education learning is conducted in accordance with the instructional materials, beginning with warm-up or gymnastics activities and followed by various games that encourage students’ active participation. Physical education is one of the subjects most favored by students because it is delivered through play-based activities. Teachers also instill health-related values and assess students based on their activeness, enthusiasm, and cooperation. However, the implementation of learning still faces challenges related to managing diverse student characteristic, indicating the need for adaptive and well-planned instructional strategies to optimize physical education learning.